Investing in Renewable Energy: Decarbonizing Power Plant Industry with the Feasibility Study of Mini-Hydro Project - Eko Tama Putra Saratian (Formosa Journal of Applied Sciences, 2023)
This study aims to analyze and determine the feasibility study of a mini-hydro project with a capacity of 2 x 3 MW in West Java, Indonesia. This research is a qualitative research with a case study approach. The selection of participants in this study used a purposive sampling technique, where the data collected was obtained from primary and secondary data. The data analysis used in this research is cash flow projection evaluation by calculating Payback-Period (PBP), Net Present Value (NPV) and Internal Rate of Return (IRR). Based on the calculations that have been made, the investment feasibility indicators for the projects to be funded are the Payback Period of 8 years and 3 months, the NPV of IDR 3,977 million and the IRR of 11.22% so that the mini-hydro project is said to be feasible to run.